Impact of Optical Imagery and Topography Data Resolution on the Measurement of Surface Fault Displacement Using Sub‐Pixel Image Correlation - Solène L. Antoine; Zhen Liu (Earth and Space Science)
Abstract The amount and spatial distribution of surface displacement that occurs during an earthquake are critical information to the understanding of the earthquake source and rupture processes. However, the earthquake surface displacement occurs over wide regions, includes multiple components that affect the ground surface at different spatial scales, and is challenging to characterize. In this study, we assess the effect of optical imagery and topography data resolution on the measurement of the earthquake surface displacement when using optical image cross‐correlation (OIC) techniques. Results show that the average noise in the output displacement maps linearly increases with decreasing image resolution, resulting in greater uncertainties in mapping surface fault geometry and associated displacement. Consequently, we observe, on average, a decrease by a factor ∼0.7–0.8 of the measured horizontal displacement when using 10 m compared to 0.5 m resolution imagery. Our analysis suggests that optical images of resolution of ≤1 m are necessary to accurately capture the complexity of the ground change. Sub‐meter vertical accuracy for the digital surface/elevation model is also required to perform accurate image orthorectification and OIC, which is better achieved in high‐resolution stereo optical imagery compared to existing global topography data. Sub‐meter resolution and stereo configurations are thus required for both the pre‐and the post‐earthquake periods to measure the full 3D near‐fault displacement field, including the vertical component using Digital Surface Model difference methods. Together, these results highlight the measurement needs for improving the observation of earthquake surface displacement toward the development of future Earth surface topography and topography change observing systems.